Assessment of Attitudes towards E-cigarettes Smoking among Middle School Students in Baghdad City/ Iraq - Asaad Salim Mohammed; Mahdi Abed Neamah (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aims: This study aims to assess attitudes of the middle school students about e-cigarette smoking; anddetermine the association between attitudes of the students with their socio-demographic characteristics.Methodology: A descriptive study used assessment approach with questionnaire items is conducted toexplore students’ knowledge related to e-cigarette smoking. By an intentional sample of (420) studentsis selected throughout the use of non-probability sampling approach. Data was collection through the useof a questionnaire and self-report. Through the application the descriptive and dedicative statistic, datawere analyzed. Results: Recent findings indicate that overall (87.4%) of students were moderate level ofattitudes. Students residency has been associated with their attitudes at p-value <0.05. Conclusion: Studentsof secondary school showing moderate level of attitudes towards E-cigarette smoking. Students’ attitudescorrelated positively with their residency. Health instructional materials such as pamphlet and bookletsshould be directed more towards smokers individual and Ministry of Education should devote more materialsin the school curricula that shed the light on the detrimental effects of smoking of all types and their risks.